The Role of Artificial Intelligence in The Decision-Making Process at The Ministry of Interior in The United Arab Emirates - Shaikha Saif Almansoori; Ali Nasser Ali Al-tahitah (Journal of Almaarif University College, 2024)
This research paper is part of an extensive study conducted by the researcher on the UAE strategy for artificial intelligence, and its role in changing the mechanism of government services, leading to a complete data analysis by 2031, according to the latest techniques and tools of artificial intelligence and their application in various fields of work efficiently. The problems of smart devices lie in the bubble filter phenomenon, which causes a lack of elasticity, increased systemic fragility, which can have serious and unexpected systemic effects. The paper objectives were; to discuss the decision-making process and the employment of artificial intelligence in the United Arab Emirates. Through the Descriptive Analytical method, the topic was presented in two sections. The discussions showed that the UAE's strategy for artificial intelligence targets several vital sectors in the country, including the transportation sector, by reducing accidents and operational costs. The health sector by reducing the proportion of chronic and dangerous diseases. The space sector conducts accurate experiments and reduces costly errors. Energy sector through utility management and smart consumption. The water sector by conducting accurate analysis and studies to save resources. The technology sector by raising the rate of production and helping in public spending, the education sector by reducing costs and increasing the desire to learn. The environment sector by increasing the proportion of afforestation and planting suitable plants. Traffic Sector Develop preventive mechanisms such as predicting accidents and traffic congestion, and setting more effective traffic policies. With the presence of the infrastructure and knowledge in the successful recruitment of artificial intelligence in the Ministry of Interior in the United Arab Emirates.